2010
DOI: 10.1097/nen.0b013e3181f97392
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stem Cells Infiltrate the Spinal Cord, Reduce Demyelination, and Localize to White Matter Lesions in Experimental Autoimmune Encephalomyelitis

Abstract: Mesenchymal stem cells (MSCs) can abrogate the animal model of multiple sclerosis, experimental autoimmune encephalomyelitis (EAE), but whether this therapeutic effect occurs entirely through systemic immune modulation and whether CNS infiltration occurs after peripheral delivery are uncertain. We studied the clinical and neuropathologic effects of intravenously administered human MSCs (hMSCs) in C57BL/6 mice with EAE. Human MSCs significantly reduced the clinical disease severity, particularly in later diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 57 publications
0
45
2
1
Order By: Relevance
“…Previous studies showed that the transplantation of various types of stem cells and their derivatives, including human bone marrow mesenchymal stem cells (BMMSCs) (3,4) adipogenic stem cells (5), placenta-derived stem cells (6), and neural precursor cells (7), promotes functional recovery in animal models of MS. However, the results of most studies indicate that the engrafted cells undergo minimal differentiation in vivo and survive for only short periods of time.…”
Section: Ultiple Sclerosis (Ms) and Its Animal Model Experimental mentioning
confidence: 99%
“…Previous studies showed that the transplantation of various types of stem cells and their derivatives, including human bone marrow mesenchymal stem cells (BMMSCs) (3,4) adipogenic stem cells (5), placenta-derived stem cells (6), and neural precursor cells (7), promotes functional recovery in animal models of MS. However, the results of most studies indicate that the engrafted cells undergo minimal differentiation in vivo and survive for only short periods of time.…”
Section: Ultiple Sclerosis (Ms) and Its Animal Model Experimental mentioning
confidence: 99%
“…Then they were incubated overnight at 4掳C with the mouse antihuman Golgi zone (Chemicon International, Temecula, CA, USA) diluted at 1/500 in blocking solution (as described by Gordon et al). 28 Slides were mounted in Vectashield containing 4,6-diamidino-2-phenylindole (DAPI; Vector Laboratories).…”
Section: Immunohistochemistry Stainingmentioning
confidence: 99%
“…In EAE model, disease commences by auto-reactive T cells that when are peripherally activated, translocate into CNS, where they are re-activated by local antigen-presenting cells, and recruit additional peripheral pathogenic immune cells to contribute to the demolition of myelin and eventual neurodegeneration (Goverman 2009). Many studies showed that transplantation of BM-MSCs modulates CD4 + T-cell-mediated myelin oligodendroglial glycoprotein peptide ) EAE, and blocks the autoimmune attack against myelin antigens (Zappia et al 2005;Gerdoni et al 2007;Gordon et al 2010;Uccelli and Prockop 2010). These effects were also correlated with reduction of demyelination as well as T-cell infiltration and induction of T-cell anergy and nervous tissue repair by integration into the CNS (Zappia et al 2005;Rafei et al 2009;Gordon et al 2010).…”
Section: Bone Marrow-derived Mscsmentioning
confidence: 99%
“…Many studies showed that transplantation of BM-MSCs modulates CD4 + T-cell-mediated myelin oligodendroglial glycoprotein peptide ) EAE, and blocks the autoimmune attack against myelin antigens (Zappia et al 2005;Gerdoni et al 2007;Gordon et al 2010;Uccelli and Prockop 2010). These effects were also correlated with reduction of demyelination as well as T-cell infiltration and induction of T-cell anergy and nervous tissue repair by integration into the CNS (Zappia et al 2005;Rafei et al 2009;Gordon et al 2010). In addition, several evidence suppose that transplanted BM-MSCs can protect neural tissue through cell replacement and/or paracrine mechanisms (Uccelli et al 2008;Uccelli and Prockop 2010); however, it is unclear whether the paracrine factors alone, without the cell graft, would exert therapeutic effect in EAE treatment.…”
Section: Bone Marrow-derived Mscsmentioning
confidence: 99%